2020
DOI: 10.1177/1078155220918627
|View full text |Cite
|
Sign up to set email alerts
|

Follicular lymphoma generating in a patient with non-small cell lung cancer following nivolumab discontinuation

Abstract: Introduction Immune checkpoint inhibitors have demonstrated the benefit for many cancer types, melanoma, non-small cell lung cancer, urothelial cancer, renal cell cancer, etc. Especially in advanced non-small cell lung cancer, significant improvement in survival results has been shown. Case Report Here, we report a 66-year-old man with lung adenocarcinoma who received nivolumab for 80 cycles. Management and Outcome: Two months after discontinuing nivolumab, he developed follicular lymphoma. Pneumonitis was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, the mechanisms underlying the development and exacerbation of B-cell lymphoma by ICI remain unclear. Two studies have reported the development of lymphoma after the cessation of ICI therapy ( 8 , 13 ) and one suggested that nivolumab treatment might inhibit the development of lymphoma ( 8 ) Moreover, the development of B-cell lymphoma after ICI treatment requires a long time. Previous studies have reported 80 cycles of treatment, 27 cycles of nivolumab, and approximately 2 years from pembrolizumab commencement ( 8 , 9 , 14 ) for the development of B-cell lymphoma, indicating that ICIs were not a direct cause of lymphoma development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanisms underlying the development and exacerbation of B-cell lymphoma by ICI remain unclear. Two studies have reported the development of lymphoma after the cessation of ICI therapy ( 8 , 13 ) and one suggested that nivolumab treatment might inhibit the development of lymphoma ( 8 ) Moreover, the development of B-cell lymphoma after ICI treatment requires a long time. Previous studies have reported 80 cycles of treatment, 27 cycles of nivolumab, and approximately 2 years from pembrolizumab commencement ( 8 , 9 , 14 ) for the development of B-cell lymphoma, indicating that ICIs were not a direct cause of lymphoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported the development of lymphoma after the cessation of ICI therapy ( 8 , 13 ) and one suggested that nivolumab treatment might inhibit the development of lymphoma ( 8 ) Moreover, the development of B-cell lymphoma after ICI treatment requires a long time. Previous studies have reported 80 cycles of treatment, 27 cycles of nivolumab, and approximately 2 years from pembrolizumab commencement ( 8 , 9 , 14 ) for the development of B-cell lymphoma, indicating that ICIs were not a direct cause of lymphoma development. However, the development and exacerbation of lymphoma during one case of pembrolizumab treatment suggested that the mechanism of exacerbation might be the depression of follicular helper T-cells and follicular regulatory T-cells induced by anti-PD-1( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation